Application of Traditional Games: How Does It Affect the Children's Fundamental Motor Skills? - Rifqi Festiawan (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
This study aims to determine the effect of implementing traditional game learning models on improving basic motor skills in children. The research method used is the experimental method. The designs used are the Pre-test and Post-test Group Design. The study population consisted of two classes with a total of 60 students and the sampling technique used simple random sampling with a sample size of 30 students. The test instruments used in this study included: 1) 4 x 10-meter shuttle run test, 2) throw-and-catch test at a distance of 1 meter from the wall, 3) Stork stand test positional balance, 4.) Test 30 sprint meter. The data analysis technique used is the prerequisite test which includes data normality test and data homogeneity test, as well as hypothesis testing using paired t-test. The results showed that there was an effect of traditional game-based learning models on the improvement of children's Fundamental Motor Skills as evidenced by p-value = 0.001. In addition, from the control group data, it is known that there is no significant effect of conventional learning on improving children's Fundamental Motor Skills as evidenced by p-value = 0.072, with these results it can be concluded that traditional game-based learning models are proven to improve children's fundamental motor skills, and can be used as an alternative to the learning process that is more effective than conventional learning.